In vitro studies of solution precursor plasma‐sprayed copper‐doped hydroxyapatite coatings with increasing copper content. Issue 6 (24th February 2020) - Unabia, Romnick B.; Candidato, Rolando T.; Pawłowski, Lech; Salvatori, Roberta; Bellucci, Devis; Cannillo, Valeria
Abstract: In this present study, in vitro characterization on bioactivity and biocompatibility of the copper‐doped hydroxyapatite (Cu‐HA) coatings deposited onto Ti6Al4V alloy with increasing copper content obtained using solution precursor plasma spray process were evaluated under simulated body fluid (SBF) and cytotoxicity tests. The growth of flake‐like structures was observed at the coatings' surface after 7 days of immersion in SBF. Elemental composition analysis showed a calcium‐deficient carbonate‐containing apatite for the grown layer. Broadening of the HA peaks were also observed in the X‐ray diffraction patterns and infrared absorption spectra of the immersed coatings associated with the possible formation of an amorphous layer at the surface of the coatings. Copper incorporation does not alter the bioactivity of HA but only slowed down for 10 mol% copper content. Cytotoxicity evaluation using MTT assays showed that 3 mol% Cu‐HA coating was not toxic under in vitro characterizations.